Membuat Game 3d Survival Horror “Suanggi Survival Papua” Berbasis Desktop Menggunakan Unity - Aris Hadisopiyan; Christian Dwi Suhendra; Parma Hadi Rantelinggi (Faculty of Computer Science, University of Jember, 2020)
Game is an activity that aims to have fun, light exercise, fill spare time, and sometimes used as a means of education. One of the most downloaded desktop games is a game made in Indonesia with the survival horror genre made with Unity. Unity is a user-friendly game engine that supports more than 25 platforms and provides many ready-to-use assets. The authors made a desktop-based 3d game with the survival horror genre made with Unity. The method used in this game's manufacture and design is the Multimedia Development Life Cycle, which has six stages, namely Concept, Design, Material Collecting, Assembly, Testing, and Distribution. In making this game using Blender, Camtasia Studio, Adobe Photoshop, Unity, Inno Setup, and the C# programming language. The program function testing phase has been successful using the black box method, and from this research, a 3d game called